2012
DOI: 10.1007/s10464-012-9529-3
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Youth Access to Alcohol: Findings from a Community‐Based Randomized Trial

Abstract: Underage drinking continues to be an important public health problem and a challenge to the substance abuse prevention field. Community-based interventions designed to more rigorously control underage access to alcohol through retailer education and greater enforcement of underage drinking laws have been advocated as potentially effective strategies to help address this problem, but studies designed to evaluate such interventions are sparse. To address this issue we conducted a randomized trial involving 36 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 17 publications
1
42
0
Order By: Relevance
“…Limited research has found that situational (e.g., lack of adult supervision, alcohol availability, and lack of enforcement) and social (e.g., group size) context characteristics contribute to increased adolescent alcohol use (Bersamin et al, 2016; Grune et al, 2017; Jackson et al, 2016; Lipperman-Kreda et al, 2015). Characteristics of drinking or substance use contexts may influence alcohol or substance use and problems through increased access and opportunities to engage in risky behaviors (Flewelling et al, 2013; Ryan et al, 2010) or through social modeling, social pressure, or social norms (Chan et al, 2017; Handren et al, 2016). If we understand the situational and social contexts in which young people are likely to use substances simultaneously and experience problems, we can develop interventions that target use and risks within these contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Limited research has found that situational (e.g., lack of adult supervision, alcohol availability, and lack of enforcement) and social (e.g., group size) context characteristics contribute to increased adolescent alcohol use (Bersamin et al, 2016; Grune et al, 2017; Jackson et al, 2016; Lipperman-Kreda et al, 2015). Characteristics of drinking or substance use contexts may influence alcohol or substance use and problems through increased access and opportunities to engage in risky behaviors (Flewelling et al, 2013; Ryan et al, 2010) or through social modeling, social pressure, or social norms (Chan et al, 2017; Handren et al, 2016). If we understand the situational and social contexts in which young people are likely to use substances simultaneously and experience problems, we can develop interventions that target use and risks within these contexts.…”
Section: Introductionmentioning
confidence: 99%
“…RYAA consisted of: reward and reminder visits to alcohol outlets, media advocacy (including articles in local papers and school newsletters on underage drinking); enforcement (compliance checks in alcohol outlets); and community coordination (including presentations and training). The evaluation consisted of annual surveys of 11th grade students and alcohol purchase surveys (decoy buyers) (Flewelling et al, 2013). Consistent with other studies, the intervention was found to be particularly effective in reducing sales to minors but did not impact on perceived availability or self-reported drinking.…”
Section: Reducing Access In the Communitymentioning
confidence: 57%
“…This is reflected in the fact that those programs which have been effective have had clearly defined messages and interventions for each target group; for example, the implementation of SPF in Eau Claire County (Eddy et al, 2012); and in the conclusion by those who have evaluated enforcement approaches to underage supply that there is a need to concurrently address formal and informal supply (SchellemanOffermans et al, 2012, Flewelling et al, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a control group, however, makes interpretation of these results difficult. Positive results were also found in a multisite randomized trial in 36 Oregon communities that tested a comprehensive intervention that included a mystery shop program, but also enforcement compliance checks, media, and other community strategies [32]. ID-checking increased by 18% in intervention communities compared with 9% in control communities.…”
Section: Introductionmentioning
confidence: 95%